Graphite graded impregnation method, method for preparing flexible high thermal conductivity graphene, and graphene
Through the graphite graded impregnation method and microtube injection technology, combined with functionalization treatment, the problems of uneven normal impregnation and large porosity of graphite in the existing technology were solved, and graphene with high thermal conductivity and flexibility was successfully prepared.
Patent Information
- Application Number
- CN202211460289.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-11-17
AI Technical Summary
In the prior art, graphite normal impregnation is uneven and porosity is large, making it difficult to prepare flexible high thermal conductivity graphene.
Using the graphite graded impregnation method, through multiple impregnation cycles, graphite slurries of different sizes are used to grade and fill in order from high to low size, combined with microtube injection technology and functionalization treatment, to form a directional arranged graphite fiber structure.
The structural stability and porosity reduction of graphite materials are achieved, the impregnation efficiency and uniformity are improved, and the thermal conductivity and flexibility of flexible high thermal conductivity graphene are enhanced.
Smart Images

Figure CN115897223B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and in particular relates to a graphite graded impregnation method, a method for preparing flexible high-thermal conductive graphene, and graphene. Background Art
[0002] Carbon / carbon composite materials (cc composite or carbon-carbon composite material) are carbon matrix composite materials reinforced by carbon fiber and its fabric. They have low density (<2.0g / cm 3 ), high strength, high specific modulus, high thermal conductivity, low expansion coefficient, good friction performance, good thermal shock resistance, high dimensional stability and other advantages. It is one of the few alternative materials used above 1650℃ today. The highest theoretical temperature is as high as 2600℃, so it is considered to be one of the most promising high-temperature materials. As an important member of the carbon fiber composite family, C / C composite material has the characteristics of low density, high specific strength and modulus, high thermal conductivity, low thermal expansion coefficient, good fracture toughness, wear resistance, and ablation resistance. In particular, its strength will not decrease but may increase with the increase of temperature. It is the material with the best high temperature resistance among all known materials. Therefore, it is widely used in various fields such as aerospace, aviation, nuclear energy, chemical industry, and medicine.
[0003] The usual preparation of carbon-carbon composite materials is a type of composite material with carbon fiber as reinforcement and carbon as matrix. Carbon fiber as reinforcement can be used in various forms and types, either chopped fiber, continuous long fiber and woven fabric. Various types of carbon fiber can be used as reinforcement for C / C composite materials. The carbon matrix can be pyrolytic carbon prepared by chemical vapor deposition, or solid carbon formed by pyrolysis of polymer materials. However, whether it is pyrolytic carbon prepared by chemical vapor deposition or solid carbon formed by pyrolysis of polymer materials, both have an obvious defect, that is, the obtained composite materials usually belong to the range of "hard carbon". It is called hard carbon because it is relatively hard in texture and is used more as a pressure-bearing part in specific application scenarios. At present, there is relatively little research on flexible carbon-carbon composite materials. This is because due to the limitations of the impregnation process, once the graphite fiber is compounded with a carbon source such as asphalt, due to the high viscosity of asphalt, the density of the carbon-carbon composite material obtained after compounding is large, which makes the material lose its flexibility.
[0004] On the other hand, the composition and structure of the impregnant in the liquid phase impregnation method are very important, which not only affects the densification efficiency, but also affects the mechanical and physical properties of the product. Improving the carbonization yield of the impregnant and reducing the viscosity of the impregnant have always been one of the key issues to be solved in the preparation of C / C composites by the liquid phase impregnation method. The high viscosity and low carbonization yield of the impregnant are one of the important reasons for the high cost of C / C composites.
[0005] Graphene slurry is a potential reagent with low viscosity and high carbonization yield. In view of the above problems, graphene slurry is an ideal impregnation reagent. By adjusting the graphene slurry system and optimizing the impregnation process, with the help of the high thermal conductivity of graphene itself, a structurally controllable high thermal conductivity flexible carbon-carbon composite material can be obtained.
[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0007] In order to solve the technical problems of uneven normal (Z-direction) impregnation and large porosity of graphite in the prior art, a graphite graded impregnation method, a method for preparing flexible high thermal conductivity graphene and graphene are provided.
[0008] The first aspect of the present invention provides a graphite graded impregnation method, comprising at least two impregnation cycles, each of which comprises: filling an impregnation slurry into a modified graphite fiber material along the direction of the graphite fiber, and adding the impregnation slurry to the inside of the filled modified graphite fiber material, and completing the impregnation after post-treatment.
[0009] Preferably, the graphite fiber is graphite felt, including but not limited to asphalt-based, polyacrylonitrile-based graphite felt and viscose-based graphite felt, etc.; further preferably, the fibers in the selected graphite felt are mainly oriented in the normal direction (Z direction), the fiber diameter is between 10 and 20 μm, the fiber length is between 100 and 200 μm, the pore size range is between 10 and 60 μm, and the volume density is between 0.1 and 0.2 g / cm 3 .
[0010] In some embodiments, as the impregnation period increases, the size of the impregnation slurry gradually decreases.
[0011] In some embodiments, three impregnation cycles are included, namely a first impregnation cycle, a second impregnation cycle and a third impregnation cycle, the impregnation slurry used in the first impregnation cycle is a large-sized impregnation slurry, the impregnation slurry used in the second impregnation cycle is a medium-sized impregnation slurry, and the impregnation slurry used in the third impregnation cycle is a small-sized impregnation slurry;
[0012] The average size of the core graphite material in the large-size impregnation slurry is 20 to 50 μm;
[0013] The average size of the core graphite material in the medium-sized impregnation slurry is 1 to 20 μm;
[0014] The average size of the core graphite material in the large-size impregnation slurry is 0.5-1 μm.
[0015] In some embodiments, the impregnation slurry further comprises an additive, and the ratio of the core graphite material to the additive is (10-100):1;
[0016] And / or, the solid content of the large-sized impregnation slurry is 0.5-1wt%, the solid content of the medium-sized impregnation slurry is 0.5-0.8wt%, and the solid content of the small-sized impregnation slurry is 0.6-1wt%.
[0017] Preferably, the additive is selected from polyacrylamide, polyvinyl alcohol, polypropylene or a combination of several thereof.
[0018] Further preferably, the molecular weights of polyacrylamide, polyvinyl alcohol, and polypropylene used in the large-size impregnation slurry are 8 million to 12 million, 250,000 to 300,000, and 400,000 to 500,000, respectively;
[0019] The molecular weights of polyacrylamide, polyvinyl alcohol, and polypropylene used in the medium-sized impregnation slurry are 6 million to 8 million, 170,000 to 220,000, and 200,000 to 400,000, respectively;
[0020] The molecular weights of polyacrylamide, polyvinyl alcohol and polypropylene used in the small-size impregnation slurry are 4 million to 6 million, 120,000 to 170,000 and 100,000 to 200,000 respectively.
[0021] In some embodiments, the post-treatment includes pressurization, heating, pressure maintenance, pressure relief, cooling, and drying, and each step of the post-treatment is performed at least once. Due to the low solid content of the slurry itself, a single impregnation can only impregnate a small part of the graphene, and multiple impregnations can achieve a better impregnation effect.
[0022] In some embodiments, the pressurized pressure is 0.5 MPa to 10 MPa;
[0023] And / or, the heating temperature is 80-150°C;
[0024] And / or, the pressure holding time is 1 to 2 hours;
[0025] And / or, the pressure relief rate is 0.05-0.1 MPa / min;
[0026] And / or, the temperature is lowered to 25-30°C.
[0027] Heating and impregnating under certain temperature conditions is beneficial to promoting the cross-linking reaction between the graphite fiber and the impregnation slurry in the modified graphite fiber material.
[0028] In some embodiments, the supplementation method includes: periodically injecting the impregnation slurry directly into the modified graphite fiber material through an injection device in a periodic microtube injection manner.
[0029] In some embodiments, the injection device includes a syringe and an injection array, the injection array includes a plurality of microtubes arranged in parallel, the inlet ends of the microtubes are connected to the outlet of the syringe, and the outlet ends of the microtubes respectively penetrate into the interior of the graphite fiber material along the direction of the graphite fiber. Preferably, the diameter of the microtubes is ≤φ0.5mm.
[0030] The impregnation process adopts a high-pressure periodic microtube injection graded impregnation method.
[0031] High pressure means that during the entire impregnation process, the modified graphite fiber (such as modified graphite felt) and the impregnation slurry (such as graphene slurry) are in a high-pressure closed impregnation container, and the pressure is between 0.5Mpa and 10Mpa, preferably 3-5Mpa. If the pressure is selected to be too low, the density of the final product will be insufficient, affecting the thermal conductivity; if the pressure is selected to be too high, the density of the final product will be increased, although the thermal conductivity of the sample will be improved, but at the same time it will lead to a strong rigidity of the product, which greatly reduces its flexibility.
[0032] Periodic microtube injection means that in order to ensure that graphene is fully and evenly impregnated with various parts of the modified graphite felt, and to prevent channel blockage, powdering and even disintegration caused by uneven internal stress distribution during the subsequent graphitization process caused by uniform impregnation, a periodic microtube injection process is designed. Through a thinner injection needle (such as ≤φ1.5mm), the slurry is periodically injected directly from the inside of the syringe into the modified graphite fiber material (such as modified graphite felt). Note that the main flow direction of the slurry here must be consistent with the orientation of the modified graphite fiber material, otherwise it will cause the graphene sheets to stack in a disorderly manner, hindering the impregnation process.
[0033] The whole device is cyclically depressurized / pressurized. First, the slurry is injected into the impregnation container at normal pressure. After the impregnation container is filled with the slurry, all valves are closed and the internal pressure is increased to 3-5Mpa. The pressure is maintained for 1-2 hours. While maintaining the pressure, the temperature inside the container is raised to 80-150°C to promote the cross-linking reaction between the fibers in the modified graphite felt and the impregnation slurry. The temperature is then lowered to room temperature, and then the pressure is slowly released at a rate of 1% until it returns to atmospheric pressure. The remaining solution is then removed to complete the impregnation process.
[0034] Graded impregnation refers to the whole impregnation process being carried out in batches according to the size of the core graphite material (such as core graphene) in the impregnation slurry. The primary impregnation uses larger graphene and matching polymer molecules. The main purpose of the primary impregnation is to fill the large pores in the modified graphite felt structure, stabilize the modified graphite felt skeleton, and use the orientation structure of the modified graphite felt skeleton to induce large sheets of graphene to be oriented according to the fiber orientation in the modified graphite felt. With the help of the rich oxygen-containing functional groups on the functionalized graphene, it is combined with the functional groups on the modified graphite felt. At the same time, with the help of the π-π interaction between the fiber and the graphene, the structure is further stabilized to form a preliminary graphene-fiber orientation skeleton. The polymer molecules play an additional "reinforcement" role. The second stage of impregnation uses medium-sized graphene for impregnation. The main purpose is to further fill the micropores that remain after the first stage of impregnation. When many large-scale graphene sheets and modified graphite felt fibers are stacked, a small amount of pores will still remain. Such pores need to be filled with medium-sized graphene to further improve the density of the product and improve the thermal conductivity. The third stage of impregnation uses small-sized graphene. The third stage of impregnation mainly uses smaller graphene nanosheets to optimize the heat conduction channel and construct a closed-cell structure. The bonding effect of small-sized graphene is more obvious. Through further filling of small-sized graphene, the disintegration and rupture of the product in the final graphitization stage can be effectively improved.
[0035] A second aspect of the present invention provides a method for preparing flexible high thermal conductivity graphene, comprising:
[0036] The graphite fiber material is functionalized to obtain a modified graphite fiber material:
[0037] The modified graphite fiber material is impregnated by the above-mentioned graphite graded impregnation method to obtain a composite graphite material;
[0038] The composite graphite material is reduced, hot-pressed and graphitized to obtain the flexible high-thermal-conductivity graphene.
[0039] Preferably, the method for functionalizing the graphite fiber material (such as graphite felt) may be an electrochemical oxidation method or a chemical oxidation method.
[0040] The parameters of the electrochemical method are: graphite felt is used as the anode, carbon rod or inert metal rod is used as the cathode, 0.5-1M dilute sulfuric acid and 0.03-0.05M dilute nitric acid are used as the electrolyte, pH value is between 0.1-1, voltage is controlled at 5-8V, current per unit mass of graphite felt is controlled at 1.5-2A / g, power is continuously applied for 0.5-1h, then the graphite felt is taken out and cleaned with water, and the modified graphite felt is obtained after vacuum drying at room temperature. Too much current will cause the graphite felt to disintegrate, and too little current will cause insufficient oxidation of the graphite felt.
[0041] The parameters of the chemical oxidation method are: add 1 part by mass of graphite felt to 5-10 parts by mass of concentrated sulfuric acid, control the temperature at 0-5°C, soak for 12 hours, then add 1-2 parts by mass of sodium nitrate and 4-6 parts by mass of potassium permanganate, heat to 35-40°C, react for 2 hours, then take out the graphite felt, wash it with clean water, and obtain the modified graphite felt after vacuum drying at room temperature.
[0042] Further preferably, after the graphite fiber (such as graphite felt) is functionalized, the hydrophilic angle is reduced from nearly 140° to below 45°, and the oxygen content after the treatment is between 5 and 8 at.%.
[0043] Preferably, the impregnated composite graphite material is reduced by a mild reducing agent such as hydroiodic acid, ascorbic acid, vitamin C, sodium borohydride, etc., and the amount of the reducing agent is equivalent to 5-20% of the mass of the composite graphite material; preferably 10wt% hydroiodic acid is used as the reducing agent, and the immersion treatment is performed for 5-8 hours to complete the reduction.
[0044] Preferably, the reduced composite graphite material is further formed by a hot pressing process to remove other functional groups and carbonize the composite graphite material as a whole. The pressing process is preferably an isostatic pressing process, the pressing pressure is between 10 and 200 MPa, preferably 25 to 50 MPa, the pressing temperature is between 500 and 800° C., preferably 600 to 700° C., and the pressing time is 30 to 500 seconds, preferably 60 to 100 seconds.
[0045] Preferably, the composite graphite material after hot pressing is subjected to a graphitization treatment process at a treatment temperature between 2600 and 3000° C., preferably between 2850 and 2950° C., to obtain the final flexible high thermal conductivity graphite material.
[0046] The third aspect of the present invention provides a flexible high thermal conductivity graphene, wherein the volume density of the flexible high thermal conductivity graphene material is 1.0 to 1.6 g / cm 3 ;
[0047] And / or, the thermal conductivity of the flexible high thermal conductivity graphene XY is 5 to 15 W / mK;
[0048] And / or, the Z-direction thermal conductivity of the flexible high thermal conductivity graphene is 12 to 50 W / mk;
[0049] And / or, the Z-direction compression rate of the flexible high thermal conductivity graphene is 5-15%;
[0050] And / or, the flexible high thermal conductivity graphene is prepared by the above-mentioned flexible high thermal conductivity graphene preparation method.
[0051] Compared with the prior art, the technical effects achieved by the present invention are as follows:
[0052] (1) The present invention uses graphite slurries of different sizes and fills them in order of size from high to low. The obtained graphite material has a stable structure and a small porosity. It is not easy to disintegrate and rupture during graphitization, so that the product has a certain flexibility.
[0053] (2) The present invention adopts a microtube injection method during the impregnation process to periodically directly inject the impregnation slurry into the interior of the graphite fiber material, so that the impregnation slurry diffuses from the interior of the graphite fiber material to the periphery, thereby increasing the impregnation efficiency and improving the uniformity of the impregnation. This solves the problem in the prior art that the impregnation slurry mainly diffuses along the periphery during the impregnation process, resulting in insufficient internal impregnation, and makes the impregnation process of the impregnation slurry (such as graphene) in the skeleton more complete.
[0054] (3) The flow direction of the impregnation slurry during the impregnation process of the present invention is consistent with the direction of the graphite fiber, so that the graphite fiber material is fully filled in the normal direction, solving the problem of low thermal conductivity in the normal direction (Z direction) of the traditional graphite thermal conductive film.
[0055] (4) The present invention uses a directional graphite fiber structure as a skeleton or template, and first functionalizes the skeleton (hydrophilicity) by electrochemical or oxidative means to obtain appropriate oxygen functional groups, thereby improving the affinity with the impregnated aqueous graphene slurry. The oxygen functional groups on the skeleton or template and the π-π interaction of the graphite hexacyclic ring are utilized to attract the functionalized graphene to be directional along the skeleton direction, thereby achieving orderly filling. The ordered arrangement makes the graphite domain structure inside the carbon-carbon composite material more complete, thereby bringing about performance improvements, especially improvement in thermal conductivity.
[0056] (5) The impregnation slurry of the present invention does not introduce asphalt, and all uses graphite phase raw materials, which have excellent high temperature resistance and can obtain graphite materials that can withstand higher operating temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a schematic diagram of the flow chart of the graphite graded impregnation method in Example 1 of the present invention;
[0058] Figure 2 is a schematic diagram of an impregnation device in Example 1 of the present invention;
[0059] Figure 3 It is a schematic diagram of the process of preparing flexible and highly thermally conductive graphene in Example 2 of the present invention;
[0060] Figure 4 It is a mechanism diagram of the core process for preparing flexible high thermal conductivity graphene in Example 2 of the present invention;
[0061] In the figure:
[0062] 101-syringe; 102-injection array; 1021-microtube; 2-chamber; 201-conventional liquid inlet; 202-conventional liquid outlet; 203-air inlet / pressure relief valve; 204-barometer; 3-modified graphite felt. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is described below by specific embodiments in conjunction with the accompanying drawings. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and is not intended to limit the order of arrangement of each method or to define the scope of implementation of the present invention. Changes or adjustments in their relative relationships can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.
[0064] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0065] Example 1: A graphite graded impregnation method
[0066] like Figure 1 , Figure 2 As shown, a graphite graded impregnation method comprises:
[0067] S1: placing the modified graphite fiber material into an impregnation device, wherein the orientation of the modified graphite fiber (modified graphite felt 3) is consistent with the main flow direction of the impregnation slurry in the subsequent impregnation device;
[0068] like Figure 2As shown, the impregnation device comprises a chamber 2, one end of the chamber 2 is a conventional liquid inlet 201, and the other end is a conventional liquid outlet 202; the impregnation device is provided with an injection device, the injection device comprises a syringe 101 and an injection array 102, the inlet of the syringe 101 is connected to the impregnation slurry supply device (not shown in the figure), the injection array 102 comprises a plurality of microtubes 1021 arranged in parallel, the inlet end of the microtube 1021 is connected to the outlet of the syringe 101, and the outlet end of the microtube 1021 respectively penetrates into the interior of the graphite fiber material; the impregnation device is also provided with an air intake / pressure relief valve 203 and a barometer 204, the air intake / pressure relief valve 203 is used to intake air for pressurization or exhaust air for pressure relief, and the pressure in the chamber of the impregnation device is displayed by the barometer 204; the impregnation device is also provided with a heating device and a thermometer (both not shown), the impregnation slurry is heated by the heating device, and the temperature of the impregnation slurry is displayed by the thermometer.
[0069] S2: Open the conventional liquid inlet 201, fill the impregnation slurry along the direction of the graphite fiber, until the impregnation slurry fills the chamber of the impregnation device, and the excess impregnation slurry flows out from the conventional liquid outlet 202;
[0070] S3: periodically injecting the impregnation slurry into the modified graphite fiber through the above-mentioned injection device, and the single injection time is 10 to 20 minutes;
[0071] S4: Close all valves, pressurize the inside of the impregnation device to 0.5Mpa-10Mpa, maintain the pressure for 1-2 hours, and heat the impregnation slurry to 80-150°C while maintaining the pressure to promote the cross-linking reaction between the modified graphite fiber and the impregnation slurry;
[0072] S5: After the reaction is completed, the temperature is lowered to room temperature, and then the impregnation slurry is slowly depressurized at a rate of 1% until it returns to atmospheric pressure, and then the remaining impregnation slurry is removed, and the temperature is controlled at 60° C. to fully dry the graphite fiber;
[0073] S6: After repeating the above steps S4 to S5 for several times (n times), for example, after repeating 10 times, the temperature is lowered to room temperature to complete the primary impregnation;
[0074] S7: Replace the impregnation slurry with a smaller size, repeat the above steps S2 to S5, and complete the secondary impregnation;
[0075] S8: According to actual needs, repeat step S7 several times (m times) to perform several levels of impregnation, such as three levels of impregnation, to complete the entire impregnation process of graphite.
[0076] Example 2: A method for preparing flexible high thermal conductivity graphene
[0077] Polyacrylonitrile-based graphite felt is used, and the main orientation of the carbon fibers in the graphite felt is normal (Z direction). The average diameter of the carbon fibers is 15μm, the average fiber length is 145μm, the average pore size is 45μm, and the volume density is 0.18g / cm 3 .
[0078] A method for preparing flexible high thermal conductivity graphene, such as Figure 3 , Figure 4 As shown, the following steps are included:
[0079] (1) Functionalization
[0080] The graphite felt is electrochemically functionalized, with the graphite felt as an anode and the carbon rod as a cathode, 1M dilute sulfuric acid and 0.05M dilute nitric acid as electrolytes, a pH value of 0.5, a voltage of 5V, and a current per unit mass of the graphite felt of 1.8A / g, and the power is continuously applied for 30 minutes, then the graphite felt is taken out and cleaned with clean water, and then vacuum dried at room temperature to obtain a modified graphite felt, and the obtained graphite felt has an oxygen content of 8at.%;
[0081] (2) Primary impregnation / drying
[0082] The modified graphite felt is placed in an impregnation device, and the first-level impregnation is performed according to the method of Example 1, and a large-size graphene slurry is selected as an impregnation agent, wherein the average size of the graphene is 28 μm, the additive is polyacrylamide (molecular weight 10 million), the ratio of graphene to the additive is 20:1, and the overall solid content of the slurry is 0.5 wt%; the slurry is injected into a container at normal pressure, and after the container is filled with the slurry, all valves are closed, and the internal pressure is increased to 5 MPa, and the temperature inside the container is raised to 100° C., and the reaction is performed for 2 hours;
[0083] Then, the pressure is slowly released at a rate of 1% until it returns to atmospheric pressure, and then the remaining solution is removed, and the temperature is controlled at 60°C to fully dry the graphite felt. This is repeated 10 times to complete the primary impregnation process;
[0084] (3) Secondary impregnation / drying
[0085] Then, a secondary impregnation was performed, and a medium-sized graphene slurry was selected as the impregnation agent. The average size of the graphene was 15 μm, the additive was polyacrylamide (molecular weight 6 million), the ratio of graphene to the additive was 20:1, and the overall solid content of the slurry was 0.6 wt%. According to the primary impregnation conditions, it was repeated 10 times to complete the secondary impregnation process;
[0086] (4) Three-stage impregnation / drying
[0087] Then, a third-stage impregnation is performed, and a small-sized graphene slurry is selected as the impregnation agent. The average size of the graphene is 0.8 μm, the additive is polyacrylamide (molecular weight 4 million), the ratio of graphene to the additive is 20:1, and the overall solid content of the slurry is 0.7 wt%. The first two-stage impregnation conditions are still followed, and the three-stage impregnation process is repeated 10 times to complete;
[0088] (5) Reduction and pressing
[0089] The impregnated composite graphite material was soaked for 5 hours at a ratio of 1 part of hydroiodic acid per 10 parts of the composite graphite material, and then the reduced composite graphite material was subjected to isostatic pressing at a pressure of 70 MPa and a pressing temperature of 650° C. for 100 seconds;
[0090] (6) Graphitization treatment:
[0091] The hot-pressed composite graphite material is further graphitized at 2850°C to obtain a flexible high thermal conductivity graphite material.
[0092] The volume density of the flexible high thermal conductivity graphite material obtained above is 1.52 g / cm 3 , the Z-direction thermal conductivity is 35W / mk, the XY-direction thermal conductivity is 15W / mk, and the Z-direction compression rate is 10%.
[0093] Example 3: A method for preparing flexible high thermal conductivity graphene
[0094] Polyacrylonitrile-based graphite felt is selected, and the main orientation of the carbon fibers in the graphite felt is normal (Z direction). The average diameter of the carbon fibers is 18μm, the average fiber length is 155μm, the average pore size is 50μm, and the volume density is 0.16g / cm 3. The graphite felt was electrochemically functionalized, with the graphite felt as the anode and the carbon rod as the cathode, 1M dilute sulfuric acid and 0.05M dilute nitric acid as the electrolyte, the pH value was 0.5, the voltage was controlled at 5V, the current per unit mass of the graphite felt was controlled at 1.7A / g, and the power was continuously turned on for 30min. Then the graphite felt was taken out and cleaned with clean water. After vacuum drying at room temperature, the modified graphite felt was obtained, and the oxygen content of the obtained graphite felt was 8at.%. Then the modified graphite felt was placed in an impregnation device for primary impregnation, and a large-size graphene slurry was selected as the impregnation agent. The average size of the graphene was 25μm, the additive was polyacrylamide (molecular weight 11 million), the ratio of graphene to additive was 15:1, and the overall solid content of the slurry was 0.5wt%. The above slurry was injected into the container at normal pressure. After the container was filled with slurry, all valves were closed, and the internal pressure began to be increased to 4.5Mpa. At the same time, the temperature inside the container was raised to 120℃ and the reaction was carried out for 2 hours. Then slowly release the pressure at a rate of 1% until it returns to atmospheric pressure, then remove the remaining solution, and control the temperature at 60°C to fully dry the graphite felt, repeat 10 times, and complete the primary impregnation process. Then carry out secondary impregnation, select medium-sized graphene slurry as the impregnation agent, the average size of the graphene is 15μm, the additive is polyacrylamide (molecular weight 6 million), the ratio of graphene to additive is 20:1, and the overall solid content of the slurry is 0.5wt%. According to the primary impregnation conditions, repeat 15 times to complete the secondary impregnation process. Then carry out tertiary impregnation, select small-sized graphene slurry as the impregnation agent, the average size of the graphene is 0.6μm, the additive is polyacrylamide (molecular weight 4 million), the ratio of graphene to additive is 20:1, and the overall solid content of the slurry is 0.8wt%. Still according to the impregnation conditions of the first two stages, repeat 10 times to complete the tertiary impregnation process. Then, the impregnated composite graphite material was soaked for 5 hours at a ratio of 1 part of hydroiodic acid per 10 parts of composite graphite material. The reduced composite graphite material was then subjected to isostatic pressing at a pressure of 65Mpa. The pressing temperature was 600°C and the pressing lasted for 90 seconds. The hot-pressed composite graphite material was further graphitized at 2850°C to obtain a flexible high thermal conductivity graphite material with a volume density of 1.56g / cm 3 , the Z thermal conductivity is 3 5W / mk, XY thermal conductivity is 18W / mk, and Z-axis compression is 8%.
[0095] Example 4: A method for preparing flexible high thermal conductivity graphene
[0096] Polyacrylonitrile-based graphite felt is used, and the main orientation of the carbon fibers in the graphite felt is normal (Z direction). The average diameter of the carbon fibers is 15μm, the average fiber length is 175μm, the average pore size is 45μm, and the volume density is 0.17g / cm 3. The graphite felt is electrochemically functionalized, with the graphite felt as the anode and the carbon rod as the cathode, with 0.8M dilute sulfuric acid and 0.04M dilute nitric acid as the electrolyte, the pH value is 0.8, the voltage is controlled at 6V, the current per unit mass of the graphite felt is controlled at 1.5A / g, and the power is continuously turned on for 30min. Then the graphite felt is taken out and cleaned with clean water. After vacuum drying at room temperature, the modified graphite felt can be obtained, and the oxygen content of the obtained graphite felt is 7at.%. The modified graphite felt is then placed in an impregnation device for primary impregnation, and a large-size graphene slurry is selected as the impregnation agent. The average size of the graphene is 25μm, the additive is polyacrylamide (molecular weight 12 million), the ratio of graphene to additive is 15:1, and the overall solid content of the slurry is 0.5wt%. The above slurry is injected into the container at normal pressure. After the container is filled with slurry, all valves are closed, and the internal pressure is increased to 5Mpa. At the same time, the temperature inside the container is raised to 150°C and the reaction is carried out for 2 hours. Then slowly release the pressure at a rate of 1% until it returns to atmospheric pressure, then remove the remaining solution, and control the temperature at 60°C to fully dry the graphite felt, repeat 10 times, and complete the primary impregnation process. Then carry out secondary impregnation, select medium-sized graphene slurry as the impregnation agent, the average size of the graphene is 15μm, the additive is polyacrylamide (molecular weight 7 million), the ratio of graphene to additive is 20:1, and the overall solid content of the slurry is 0.5wt%. According to the primary impregnation conditions, repeat 15 times to complete the secondary impregnation process. Then carry out tertiary impregnation, select small-sized graphene slurry as the impregnation agent, the average size of the graphene is 0.6μm, the additive is polyacrylamide (molecular weight 6 million), the ratio of graphene to additive is 20:1, and the overall solid content of the slurry is 0.8wt%. Still according to the impregnation conditions of the first two stages, repeat 10 times to complete the tertiary impregnation process. Then, the impregnated composite graphite material was soaked for 5 hours at a ratio of 1 part of hydroiodic acid per 10 parts of composite graphite material. The reduced composite graphite material was then subjected to isostatic pressing at a pressure of 65Mpa. The pressing temperature was 600°C and the pressing lasted for 90 seconds. The hot-pressed composite graphite material was further graphitized at 2950°C to obtain a flexible high thermal conductivity graphite material with a volume density of 1.57g / cm 3 , the Z-direction thermal conductivity is 33W / mk, the XY-direction thermal conductivity is 16W / mk, and the Z-direction compression rate is 9%.
[0097] Example 5: A method for preparing flexible high thermal conductivity graphene
[0098] Asphalt-based graphite felt is used, and the main orientation of carbon fibers in the graphite felt is normal (Z direction). The average diameter of the carbon fibers is 12 μm, and the average fiber length is 1 3 0μm, average pore size 55μm, bulk density 0.16g / cm 3. The graphite felt is electrochemically functionalized, with the graphite felt as the anode and the carbon rod as the cathode, 0.9M dilute sulfuric acid and 0.03M dilute nitric acid as the electrolyte, the pH value is 0.5, the voltage is controlled at 5V, the current per unit mass of the graphite felt is controlled at 1.7A / g, and the power is continuously turned on for 30min. Then the graphite felt is taken out and cleaned with clean water. After vacuum drying at room temperature, the modified graphite felt can be obtained, and the oxygen content of the obtained graphite felt is 8at.%. Then the modified graphite felt is placed in an impregnation device for primary impregnation, and a large-size graphene slurry is selected as the impregnation agent. The average size of the graphene is 25μm, the additive is polyvinyl alcohol (molecular weight 260,000), the ratio of graphene to additive is 18:1, and the overall solid content of the slurry is 0.5wt%. The above slurry is injected into the container at normal pressure. After the container is filled with slurry, all valves are closed, and the internal pressure is increased to 5Mpa. At the same time, the temperature inside the container is raised to 110°C and the reaction is carried out for 2 hours. Then slowly release the pressure at a rate of 1% until it returns to atmospheric pressure, then remove the remaining solution, and control the temperature at 60 ° C, fully dry the graphite felt, repeat 10 times, and complete the primary impregnation process. Then carry out secondary impregnation, select medium-sized graphene slurry as the impregnation agent, the average size of the graphene is 14 μm, the additive is polyvinyl alcohol (molecular weight 170,000), the ratio of graphene to additive is 20: 1, and the overall solid content of the slurry is 1wt%. According to the primary impregnation conditions, repeat 15 times to complete the secondary impregnation process. Then carry out tertiary impregnation, select small-sized graphene slurry as the impregnation agent, the average size of the graphene is 0.5 μm, the additive is polyvinyl alcohol (molecular weight 120,000), the ratio of graphene to additive is 20: 1, and the overall solid content of the slurry is 0.8wt%. Still according to the impregnation conditions of the first two stages, repeat 10 times to complete the three-stage impregnation process. Then, the impregnated composite graphite material was soaked for 5 hours at a ratio of 1 part of hydroiodic acid per 10 parts of composite graphite material. The reduced composite graphite material was then subjected to isostatic pressing at a pressure of 65Mpa. The pressing temperature was 600°C and the pressing lasted for 90 seconds. The hot-pressed composite graphite material was further graphitized at 2850°C to obtain a flexible high thermal conductivity graphite material with a volume density of 1.43g / cm 3 , the Z-direction thermal conductivity is 40W / mk, the XY-direction thermal conductivity is 22W / mk, and the Z-direction compression rate is 5.5%.
[0099] Example 6: A method for preparing flexible high thermal conductivity graphene
[0100] Polyacrylonitrile-based graphite felt is used, and the main orientation of the carbon fibers in the graphite felt is normal (Z direction). The average diameter of the carbon fibers is 20 μm, the average fiber length is 180 μm, the average pore size is 60 μm, and the volume density is 0.19 g / cm 3. The graphite felt is functionalized by chemical oxidation. 1 part of graphite felt is added to 10 parts of concentrated sulfuric acid, the temperature is controlled at 0°C, and it is soaked for 12 hours. Then 2 parts of sodium nitrate and 5 parts of potassium permanganate are added, the temperature is raised to 35°C, and the reaction is carried out for 2 hours. Then the graphite felt is taken out and cleaned with clean water. After vacuum drying at room temperature, the modified graphite felt can be obtained, and the oxygen content of the obtained graphite felt is 7.5at.%. Then the modified graphite felt is placed in an impregnation device for primary impregnation. A large-size graphene slurry is selected as the impregnation agent. The average size of the graphene is 50μm, the additive is polyacrylamide (molecular weight 11 million), the ratio of graphene to additive is 15:1, and the overall solid content of the slurry is 0.5wt%. The above slurry is injected into the container at normal pressure. After the container is filled with slurry, all valves are closed, and the internal pressure is increased to 4.5Mpa. At the same time, the internal temperature of the container is increased to 120°C and the reaction is carried out for 2 hours. Then, the pressure is slowly released at a rate of 1% until it returns to atmospheric pressure, and then the remaining solution is removed, and the temperature is controlled at 60°C to fully dry the graphite felt. Repeat 15 times to complete the primary impregnation process. Then, the secondary impregnation is carried out, and a medium-sized graphene slurry is selected as the impregnation agent. The average size of the graphene is 15μm, the additive is polyacrylamide (molecular weight 6 million), the ratio of graphene to additive is 50:1, and the overall solid content of the slurry is 0.8wt%. According to the primary impregnation conditions, repeat 15 times to complete the secondary impregnation process. Then, the tertiary impregnation is carried out, and a small-sized graphene slurry is selected as the impregnation agent. The average size of the graphene is 0.6μm, the additive is polyacrylamide (molecular weight 4 million), the ratio of graphene to additive is 20:1, and the overall solid content of the slurry is 0.8wt%. Still according to the impregnation conditions of the first two stages, repeat 10 times to complete the tertiary impregnation process. Then, the impregnated composite graphite material was soaked for 5 hours at a ratio of 1 part of hydroiodic acid per 10 parts of composite graphite material. The reduced composite graphite material was then subjected to isostatic pressing at a pressure of 120 MPa. The pressing temperature was 700°C and the pressing lasted for 100 seconds. The hot-pressed composite graphite material was further graphitized at 2850°C to obtain a flexible high thermal conductivity graphite material with a volume density of 1.60 g / cm 3 , the Z-direction thermal conductivity is 45W / mk, the XY-direction thermal conductivity is 22W / mk, and the Z-direction compression rate is 6.5%.
[0101] Example 7: A method for preparing flexible high thermal conductivity graphene
[0102] Polyacrylonitrile-based graphite felt is used, and the main orientation of the carbon fibers in the graphite felt is normal (Z direction). The average diameter of the carbon fibers is 20 μm, the average fiber length is 185 μm, the average pore size is 55 μm, and the volume density is 0.2 g / cm 3. The graphite felt is electrochemically functionalized, with the graphite felt as the anode and the carbon rod as the cathode, 1M dilute sulfuric acid and 0.05M dilute nitric acid as the electrolyte, the pH value is 0.5, the voltage is controlled at 5V, the current per unit mass of the graphite felt is controlled at 1.7A / g, and the power is continuously turned on for 30min. Then the graphite felt is taken out and cleaned with clean water. After vacuum drying at room temperature, the modified graphite felt can be obtained, and the oxygen content of the obtained graphite felt is 8at.%. Then the modified graphite felt is placed in an impregnation device for primary impregnation, and a large-size graphene slurry is selected as the impregnation agent. The average size of the graphene is 25μm, the additive is polypropylene (molecular weight 500,000), the ratio of graphene to additive is 15:1, and the overall solid content of the slurry is 0.5wt%. The above slurry is injected into the container at normal pressure. After the container is filled with slurry, all valves are closed, and the internal pressure is increased to 5Mpa. At the same time, the temperature inside the container is raised to 120°C and the reaction is carried out for 2 hours. Then slowly release the pressure at a rate of 1% until it returns to atmospheric pressure, then remove the remaining solution, control the temperature at 60°C, fully dry the graphite felt, repeat 10 times, and complete the primary impregnation process. Then carry out secondary impregnation, select medium-sized graphene slurry as the impregnation agent, the average size of the graphene is 15μm, the additive is polyvinyl alcohol (molecular weight 180,000), the ratio of graphene to additive is 20:1, and the overall solid content of the slurry is 0.7wt%. According to the primary impregnation conditions, repeat 15 times to complete the secondary impregnation process. Then carry out tertiary impregnation, select small-sized graphene slurry as the impregnation agent, the average size of the graphene is 0.6μm, the additive is polyacrylamide (molecular weight 4 million), the ratio of graphene to additive is 40:1, and the overall solid content of the slurry is 0.8wt%. Still according to the impregnation conditions of the first two stages, repeat 10 times to complete the three-stage impregnation process. Then, the impregnated composite graphite material was soaked for 5 hours at a ratio of 1 part of hydroiodic acid per 15 parts of composite graphite material. The reduced composite graphite material was then subjected to isostatic pressing at a pressure of 90 MPa. The pressing temperature was 600°C and the pressing lasted for 90 seconds. The hot-pressed composite graphite material was further graphitized at 2900°C to obtain a flexible high thermal conductivity graphite material with a volume density of 1.7 g / cm 3 , the thermal conductivity in Z direction is 35W / mk, the thermal conductivity in XY direction is 18W / mk, and the compression rate in Z direction is 8%.
[0103] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A graphite graded impregnation method, characterized in that: The method comprises at least two impregnation cycles, and as the impregnation cycle increases, the size of the impregnation slurry gradually decreases, and each of the impregnation cycles comprises: filling the impregnation slurry into the modified graphite fiber material along the direction of the graphite fiber, and replenishing the impregnation slurry into the filled modified graphite fiber material, and completing the impregnation after post-treatment, wherein the post-treatment comprises pressurization, heating, pressure maintenance, pressure relief, temperature reduction, and drying, and each step of the post-treatment is performed at least once, and the pressurization pressure is 0.5MPa to 10MPa; The graphite fiber is a modified graphite fiber whose skeleton is functionalized by electrochemical or oxidative means; The product obtained by the graded impregnation method has flexibility.
2. The graphite graded impregnation method according to claim 1, characterized in that: The method comprises three impregnation cycles, namely a first impregnation cycle, a second impregnation cycle and a third impregnation cycle. The impregnation slurry used in the first impregnation cycle is a large-sized impregnation slurry, the impregnation slurry used in the second impregnation cycle is a medium-sized impregnation slurry, and the impregnation slurry used in the third impregnation cycle is a small-sized impregnation slurry.
3. The graphite graded impregnation method according to claim 2, characterized in that: The average size of the core graphite material in the large-size impregnation slurry is 20 to 50 μm; The average size of the core graphite material in the medium-sized impregnation slurry is 1 to 20 μm; The average size of the core graphite material in the small-sized impregnation slurry is 0.5-1 μm.
4. The graphite graded impregnation method according to claim 3, characterized in that: The impregnation slurry further includes an additive, and the ratio of the core graphite material to the additive is (10-100):1; And / or, the solid content of the large-sized impregnation slurry is 0.5-1wt%, the solid content of the medium-sized impregnation slurry is 0.5-0.8wt%, and the solid content of the small-sized impregnation slurry is 0.6-1wt%.
5. The graphite graded impregnation method according to claim 1, characterized in that: The heating temperature is 80-150°C; And / or, the pressure maintaining time is 1 to 2 hours.
6. The graphite graded impregnation method according to claim 1, characterized in that: The pressure relief rate is 0.05-0.1 MPa / min; And / or, the temperature is lowered to 25-30°C.
7. The graphite graded impregnation method according to claim 1, characterized in that: The method for supplementing the impregnation slurry comprises: periodically injecting the impregnation slurry directly into the modified graphite fiber material through an injection device in a periodic micro-tube injection manner.
8. The graphite graded impregnation method according to claim 7, characterized in that: The injection device comprises a syringe and an injection array. The injection array comprises a plurality of microtubes arranged in parallel. The inlet ends of the microtubes are connected to the outlets of the syringes. The outlet ends of the microtubes respectively penetrate into the interior of the graphite fiber material.
9. A method for preparing flexible high thermal conductivity graphene, characterized in that: include: Functionalizing the graphite fiber material to obtain a modified graphite fiber material; The modified graphite fiber material is impregnated by the graphite graded impregnation method according to any one of claims 1 to 8 to obtain a composite graphite material; The composite graphite material is reduced, hot-pressed and graphitized to obtain the flexible high-thermal-conductivity graphene.
10. A flexible high thermal conductivity graphene, characterized in that: The volume density of the flexible high thermal conductivity graphene is 1.0 to 1.6 g / cm 3 ; And / or, the thermal conductivity of the flexible high thermal conductivity graphene XY is 5 to 15 W / mK; And / or, the Z-direction thermal conductivity of the flexible high thermal conductivity graphene is 12 to 50 W / mK; And / or, the Z-direction compression rate of the flexible high thermal conductivity graphene is 5-15%; And / or, the flexible high thermal conductivity graphene is prepared by the method for preparing the flexible high thermal conductivity graphene according to claim 9.
Citation Information
Patent Citations
Rapid preparation method of C / C composite material
CN109384470A
Graphene fiber non-woven fabric reinforcing method and method for continuously preparing high-performance graphene non-woven fabric
CN112680957A
Modified fibre product, preparation method therefor and use thereof
WO2018166477A1